2013
DOI: 10.7771/1932-6246.1155
|View full text |Cite
|
Sign up to set email alerts
|

Solving Large Problems with a Small Working Memory

Abstract: We describe an important elaboration of our multiscale/multiresolution model for solving the Traveling Salesman Problem (TSP). Our previous model emulated the non-uniform distribution of receptors on the human retina and the shifts of visual attention. This model produced nearoptimal solutions of TSP in linear time by performing hierarchical clustering followed by a sequence of coarse-to-fine approximations of the tour. Linear time complexity was related to the minimal amount of search performed by the model, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…One promising lead comes from applications of complexity theory to cognition. For example, it has been demonstrated that spatial information processing in perception, attention, memory, and problem solving all involve a common algorithm based in grouping (Graham et al, 2000; Pizlo and Stefanov, 2013). All these functions operate by dividing a defined problem space into related clusters prior to local analysis (e.g., in PO - subsets of visual features likely to represent different objects; in selective attention - subsets of auditory or visual stimuli to group apart from others; in problem solving – dividing a larger task into coherent subtasks that can be completed efficiently, etc.).…”
Section: Discussionmentioning
confidence: 99%
“…One promising lead comes from applications of complexity theory to cognition. For example, it has been demonstrated that spatial information processing in perception, attention, memory, and problem solving all involve a common algorithm based in grouping (Graham et al, 2000; Pizlo and Stefanov, 2013). All these functions operate by dividing a defined problem space into related clusters prior to local analysis (e.g., in PO - subsets of visual features likely to represent different objects; in selective attention - subsets of auditory or visual stimuli to group apart from others; in problem solving – dividing a larger task into coherent subtasks that can be completed efficiently, etc.).…”
Section: Discussionmentioning
confidence: 99%
“…Results indicated that participants could find near-optimal solutions quickly in such a paradigm, suggesting that these decisions used shortcuts. This interpretation was further supported by the authors’ computational models which used a hierarchical clustering structure similar to how the visual system processes incoming information ( Pizlo and Stefanov, 2013 ). In this light, individual differences in demand avoidance may reflect these different strategies, with some individuals choosing a higher demanding option if they find this effort may instead save computational processing of making decisions.…”
Section: Discussionmentioning
confidence: 79%
“…These heuristics were theorized to be formed using available cues from past and current experiences and used for updating the value of these cues based on the ensuing outcome of a selected (and performed) action ( Payne et al, 1993 ). For example, one way to investigate these strategy formations is by using a computationally intractable problem or one that needs an unreasonable amount of time and effort to process every available piece of information in a problem ( Pizlo and Stefanov, 2013 ). Results indicated that participants could find near-optimal solutions quickly in such a paradigm, suggesting that these decisions used shortcuts.…”
Section: Discussionmentioning
confidence: 99%